2005
DOI: 10.1002/ijc.21097
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of p53 gene and the prognostic impact of dominant‐negative p53 mutation in endometrial cancer

Abstract: In addition to the loss of function, mutant p53 can possess a dominant-negative effect on wild-type p53 and may also exert gain-offunction activity. It is not clear whether the functional status of p53 mutation contributes to differences in outcome in endometrial cancer. We collected a total of 92 RNA samples of high quality from endometrial cancer tissues, and the samples were subjected to yeast functional assay and sequencing for p53 mutations. The detected mutant p53 genes were further investigated for thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…We have found that oral SCC patients with DNp53 mutations have a significantly worse outcome than patients with recessive mutations, in terms of recurrence free survival [Hassan et al, 2008]. This has also been noted in other cancers (Marutani et al, 1999;Sakuragi et al, 2005). The overrepresentation of DN mutants, accounting for about 27% of all p53 mutations (6414 of all 23,544 in the IARC database R11), suggests an advantage for tumour development of the cancer cell harbouring a DN mutation.…”
Section: P53supporting
confidence: 65%
“…We have found that oral SCC patients with DNp53 mutations have a significantly worse outcome than patients with recessive mutations, in terms of recurrence free survival [Hassan et al, 2008]. This has also been noted in other cancers (Marutani et al, 1999;Sakuragi et al, 2005). The overrepresentation of DN mutants, accounting for about 27% of all p53 mutations (6414 of all 23,544 in the IARC database R11), suggests an advantage for tumour development of the cancer cell harbouring a DN mutation.…”
Section: P53supporting
confidence: 65%
“…In our previous study [12], we demonstrated a strong link between DN mutant TP53 and the progression of endometrial cancer. In the present work, we focused on the precise role of DN mutant TP53 R273H in the cell invasion and migration of the endometrial cancer cell HHUA, and showed for the first time that DN mutant TP53 R273H, a TP53 missense mutation commonly found in endometrial cancer, strongly induces the invasive and migratory activities of the endometrial cancer cell HHUA.…”
Section: Discussionmentioning
confidence: 75%
“…Taken together, our findings suggested that the invasive phenotype in HHUA endometrial cancer cells was mostly given by a balance between the transdominant canceling effect of R273H and wt p53 transcriptional activity rather than a gain-of-function effect induced solely by R273H mutant p53. This may, at least in part, afford a possible molecular basis by which DN mutant p53 promotes tumor progression in patients with the advanced stages and nonendometrioid subtype of endometrial cancer [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to lower FOXO1 expression, the majority of oestrogen-related type I (endometrioid) endometrial cancers are characterised by loss or mutation of the tumour-suppressor gene PTEN, leading to enhanced activity of the PI3K/Akt signalling pathway, and further inactivation of FOXO proteins (Kong et al 1997, Risinger et al 1998. Conversely, dominant-negative TP53 mutations are often found in advanced and histological subtypes of endometrial cancer and are a strong predictor of survival (Sakuragi et al 2005). These clinico-pathological observations should accelerate research into the mechanisms that govern life and death decisions in the human endometrium.…”
Section: Perspectivementioning
confidence: 99%